SYMPHONY NO. 2 “SYMPHONY OF CHORALES” BY LUKAS FOSS: A STUDY IN COLLAGE AND MUSICAL BORROWING - Powers, Alec (East Carolina University, 2018)
In his second symphony, the Symphony of Chorales (1958), Foss seems to be struggling to merge two identities, his Stravinskian Neoclassicism and his improvisation-influenced experimentalism. The mature Foss is first able to blend these two disparate styles with the premiere of American Cantata in 1976, while his third (1991) and fourth (1995) symphonies show a mastery of this sort of collage. The second symphony is significant because it shows one of the composer's first attempts to reconcile two very disparate compositional approaches - yet this same process of eclectic reconciliation would fascinate Foss throughout the rest of his life, and impact other major works, such as Baroque Variations, American Cantata, Renaissance Concerto and many others. In this thesis, the tonal language of Foss's Symphony of Chorales will be examined within the context of his earlier and later styles, and the impact of collaged source material (Bach's chorale harmonizations) on the motivic and formal structure of the symphony will be discussed.
Keywords: Symphony of Chorales; Symphony No. 2; J.S. Bach; Stravinsky; collage; musical borrowing; Foss, Lukas, 1922-2009. Symphony of chorales; Quotation in music; Orchestral music--20th century--History and criticism